Influence of ultrasonication during soaking on water absorption and Softness characteristics in the cooking process of cowpea - Sholeh Rostamirad; K.G. Duodu; J.P. Meyer; M. Sharifpur (Ultrasonics Sonochemistry)
Owing to the long duration of cooking legumes, which limits their consumption and utilization, soaking has been used to reduce cooking time, save energy consumption, and diminish their hardness. However, limited studies have reported the influence of cooking and soaking treatment along with ultrasonication on hydration, hardness, and cooking time reduction of legumes. Therefore, this study investigated the impact of cooking and soaking treatments on Dr. Saunder cowpea’s water absorption, hardness, and cooking time reduction with and without ultrasonication. Samples of Dr. Saunder’s cowpea were first soaked at 30 °C and 50 °C for 15 – 90 min (with and without ultrasonication), after which they were cooked at 100 °C and 121 °C for 15 – 120 min. The absorbed water and hardness of the tested samples under these treatments were measured. Hydration and softening behaviors were modeled from the obtained data using Ibarz-Augusto and first-order equations, respectively. Arrhenius equation was used to describe the kinetics of the hydration and softening process. Results showed that ultrasonic treatments accelerated water absorption and reduced the hardness of the samples; consequently, in a shorter time, using less energy will receive the desired hardness as the final product. The Ibartz-Augusto and first-order equations perfectively fit the sigmoidal and decaying exponential behavior of the absorbed water and hardness data with high prediction performance (R2 ≈ 1) marked by minimal error values. The deployment of ultrasonication and increased cooking temperature were observed to reduce the kinetic parameter (water absorption) and elevate the softening rates and activation energy (for hydration and softening). A synergy of the trio treatments reduced the total cooking duration from 120 min to 90 min (25 %), thus promoting the benefit of deploying ultrasonication to soften cowpeas and other seeds rapidly.